Temporal–Spatial Dynamics and Collaborative Effects of Cropland Resilience in China - Liang Luo; Yetong Li; Wenjie Ma; Jianbo Rong; Jie Wei; Yong Cui; Tingting Qu (Land)
Cropland resilience is the ability of cropland systems to adapt and rebound from multiple stresses and disturbances. Cropland resilience is vital for ensuring national food security, promoting sustainable agricultural development, and adapting to global climate change. This study measures cropland resilience in China using the entropy method within the PSR framework. Additionally, it employs quantitative analysis methods, including kernel density estimation, the standard deviation ellipse, the Theil Index, and the geographical detector, to systematically examine the spatiotemporal dynamics of cropland resilience and its driving factors in China. The findings reveal the evolving trends of cropland resilience over time and space, highlighting regional differences and the spatial distribution of resilience. The study found the following: (1) The overall cropland resilience in China shows an upward trend, but there is uneven development among regions, particularly in the relatively lagging western areas. (2) There is a notable spatial imbalance in cropland resilience, primarily driven by intra-regional differences. (3) Stability of Grain Production; Total Grain Production; Fiscal Expenditure on Agriculture, Forestry, and Water; Soil–Water Harmony; and the Cropland Disaster Resistance Index are identified as key driving factors, with the influence of the Cropland Disaster Resistance Index notably increasing over time. (4) The study highlights the critical role of synergistic effects among these factors in enhancing cropland resilience, noting a significant strengthening of these synergies over time. The research results offer a fresh perspective on the role of cropland resilience in dynamic environments. They enhance our understanding of the spatiotemporal characteristics of cropland resilience, reveal its underlying dynamic processes, and provide a scientific basis for policymaking aimed at promoting the sustainable use and management of cropland.